Effects of Organic Acids on Salmonella enteritidis Growth Inhibition and Ileum Surface Area in Laying Ducks Fed Anaerobically Fermented Feed - Tarman , A.T. Allaily; Ramli, N.R. Nahrowi; Ridla, M.R.M.; Yaman, M.A.Y.M. Aman; Setiyono, A.S. Agus (International Journal of Poultry Science, 2017)
Objective: This study aimed to determine the organic acid content of anaerobically fermented feed, its capacity to inhibit Salmonella enteritidis and its effects on the ileum surface area of laying ducks. Materials and methods: To determine the organic acid content and inhibitory effects of fermented feed, four fermentation times were used as treatments (7, 14, 21 and 28 days) and each treatment was replicated three times. The feed ingredients included yellow corn, soybean meal, coconut meal, fish meal, CaCO3, dicalcium phosphate (DCP), premix and lactic acid bacteria at 5×108 CFU mL–1. The feed was anaerobically fermented with a moisture content of up to 45% and local 5 month old laying ducks were used. The surface area of the ileum was measured in 6.5 and 8 month old ducks assigned to the 3 treatments (R1 = Dry feed, R2 = Wet feed without fermentation, R3 = Wet anaerobically fermented feed). Ileum surface area was initially 10 cm. After treatment, the tissue was prepared with hematoxylin and eosin staining and the area was measured using ImageJ software. The measured parameters were: (1) Organic acids, (2) The inhibitory zone and (3) Ileum surface area. Results: Fermented feed contained organic acids, such as lactic acid, propionic acid and butyric acid, that inhibited pathogenic bacteria, such as S. enteritidis. Fermented feed resulted in an increase in ileum surface area. Conclusion: Anaerobically fermented feed maintained conditions that caused the ileum surface area become larger, increasing nutrient absorption.